Gender comparison of mathematics anxiety and cognitive reflection - Kan, See Kei (Universiti Malaysia Sarawak (UNIMAS), 2018)
The aim of this research is to examine differences in dependent variables which are mathematics anxiety and cognitive reflection based on gender. This research also investigated the association between mathematics anxiety and cognitive reflection. A total of 150 Cognitive Sciences undergraduate students from Universiti Malaysia Sarawak (UNIMAS)participated in this correlational and comparative survey research. In data collection, a set of questionnaire in which adapted from Mathematics Anxiety Rating Scale-Short Version (MARS-SV) and Cognitive Reflection Test-Long (CRT-L) was used. Moreover, independent t-test analyses were used to identify the differences in mathematics anxiety and cognitive reflection between male and female students. Additionally, Pearson Correlation was used to determine the relationship between mathematics anxiety and cognitive reflection. This research finding indicated that cognitive reflection was significantly different between male and female students. Male students performed better in CRT than female students. However, mathematics anxiety was not significantly different between male and female students. This research finding also demonstrated that mathematics anxiety was negatively correlated to cognitive reflection. Yet, the relationship was not significant.